Does Pharmacogenetic Testing for CYP450 2D6 and 2C19 Among Patients with Diagnoses within the Schizophrenic Spectrum Reduce Treatment Costs?. (6th July 2013) - Herbild, Louise; Andersen, Stig E.; Werge, Thomas; Rasmussen, Henrik B.; Jürgens, Gesche
Abstract: The effect of pharmacogenetic testing for CYP450 2D6 and 2C19 on treatment costs have not yet been documented. This study used Danish patient registers to calculate healthcare costs of treating patients with diagnoses within the schizophrenic spectrum for 1 year with or without pharmacogenetic testing for polymorphisms in the genes for the CYP2D6 and CYP2C19 enzymes. In a randomized, controlled trial, stratified with respect to metabolizer genotype, 104 patients were assigned to treatment based on pharmacogenetic testing and 103 patients to treatment as usual. Random exclusion of extensive and intermediate metabolizers was used to increase the frequency of extreme metabolizers (poor metabolizers and ultrarapid metabolizers for CYP2D6) to 20% in both groups. Cost differences were analysed at several levels including (i) overall healthcare expenditure, (ii) psychiatric hospital cost (iii) nonpsychiatric hospital cost, (iv) primary care spending and (v) pharmaceuticals. Statistically significant differences in costs of psychiatric care dependent on metabolizer status were found between intervention groups. Pharmacogenetic testing significantly reduced costs among the extreme metabolizers (poor metabolizers and ultrarapid metabolizers) to 28%. Use of primary care services and pharmaceuticals was also affected by the intervention.This study confirms earlier findings that extreme metabolizers (poor and ultrarapid metabolizers) incur higher costs than similar patients with a normal metabolizer genotype. However, this study shows that these excess costs can be reduced by pharmacogenetic testing. Pharmacogenetic testing for CYP2D6 and CYP2C19 could thus be considered as a means of curtailing high psychiatric treatment costs among extreme metabolizers.